2023
DOI: 10.3390/su15064729
|View full text |Cite
|
Sign up to set email alerts
|

Mindfulness Abilities Are Associated with Anxiety Levels, Emotional Intelligence, and Perceived Self-Efficacy

Abstract: This study examined the relationship between anxiety, emotional intelligence, perceived self-efficacy, and mindfulness abilities. A total of 205 Spanish university students were assessed for mindfulness (Freiburg Mindfulness Inventory-14), state-trait anxiety (State-Trait Anxiety Inventory), emotional intelligence (Trait Meta-Mood Scale-24), and general perceived self-efficacy (General Self-Efficacy Scale). The Student’s t-test was used to evaluate the possible differences between sexes for the study variables… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 58 publications
0
1
0
Order By: Relevance
“…According to the emotional competence model of Bisquerra and Pérez-Escoda (2007), these skills are part of a positive pool of resources and personal dimensions of the individual that should be enhanced, such as self-efficacy, selfesteem, and resilience. Another recent study (Martínez-Pérez et al, 2023) demonstrated the significance of perceived self-efficacy in university students in relation to other social and emotional skills important for academic performance.…”
Section: Discussionmentioning
confidence: 99%
“…According to the emotional competence model of Bisquerra and Pérez-Escoda (2007), these skills are part of a positive pool of resources and personal dimensions of the individual that should be enhanced, such as self-efficacy, selfesteem, and resilience. Another recent study (Martínez-Pérez et al, 2023) demonstrated the significance of perceived self-efficacy in university students in relation to other social and emotional skills important for academic performance.…”
Section: Discussionmentioning
confidence: 99%